Personal Branding and Integrated Marketing Communication on TikTok: The Marketing Strategy of Daviena Skincare's Owner @melvinahusyanti - Pauzana; Muhammad Junaidi; Nazhifa Alfaini (Communication Studies Program Faculty of Social and Political Sciences Universitas Nurdin Hamzah Jambi, Indonesia, 2026)
Driven by the increasing use of TikTok as a marketing communication medium by skincare brands, the account @melvinahusyanti owned by Daviena Skincare stands out among competitors. This study aims to analyze the marketing communication strategies implemented and their impact on audience responses and sales growth. This research employs a qualitative approach using content analysis. Data were collected through observation of six TikTok videos uploaded between November and December 2025, along with documentation such as screenshots, audience comments, and analysis of visual and verbal messages. The results show that the marketing communication strategy is carried out through the development of personal branding, including educational content, product promotion, storytelling, and direct interaction with the audience. This strategy has a positive impact on increasing engagement and sales. In conclusion, the effective use of TikTok with appropriate communication strategies can enhance consumer trust and loyalty. It is recommended to maintain message consistency, improve content creativity, and manage audience responses effectively to ensure alignment with the brand image.